Multipole expansion for H i intensity mapping experiments: simulations and modelling - Cunnington, Steven; Pourtsidou, Alkistis; Soares, Paula S; Blake, Chris; Bacon, David (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT We present a framework and an open-source python toolkit to analyse the two-point statistics of 3D fluctuations in the context of H i intensity maps using the multipole expansion formalism. We include simulations of the cosmological H i signal using N-body and lognormal methods, foregrounds and their removal, as well as instrumental effects. Using these simulations and analytical modelling, we investigate the impact of foreground cleaning and the instrumental beam on the power spectrum multipoles as well as on the Fourier space clustering wedges. We find that both the instrumental beam and the foreground removal can produce a quadrupole (and a hexadecapole) signal, and demonstrate the importance of controlling and accurately modelling these effects for precision radio cosmology. We conclude that these effects can be modelled with reasonable accuracy using our multipole expansion technique. We also perform a Markov Chain Monte Carlo (MCMC) analysis to showcase the effect of foreground cleaning on the estimation of the H i abundance and bias parameters. The accompanying python toolkit is available at https://github.com/IntensityTools/MultipoleExpansion, and includes an interactive suite of examples to aid new users.